Errata to "Formations of Monoids, Congruences, and Formal Languages" - A. Ballester-Bolinches; E. Cosme-Llópez; R. Esteban-Romero; J.J.M.M. Rutten (Scientific Annals of Computer Science)
[1] A. Ballester-Bolinches, E. Cosme-Llópez, R. Esteban Romero, and J.J.M.M. Rutten. Formations of monoids, congruences, and formal languages. Scientific Annals of Computer Science, 25(2):171–209, 2015. doi:10.7561/SACS.2015.2.171.